Development of microbial biosensor for the detection of paraquat [compact disc] - 614728 Mohd. Firdaus Abdul Wahab (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Science (Industrial Chemistry)) - Universiti Teknologi Malaysia, 2004